Productivity Spillovers among Knowledge Workers in Agglomerations: Evidence from GitHub - Lena Abou El-Komboz; Thomas A. Fackler; Moritz Goldbeck (CESifo GmbH, 2024)
Software engineering is prototypical of knowledge work in the digital economy and exhibits strong geographic concentration, with Silicon Valley as the epitome of a tech cluster. We investigate productivity effects of knowledge worker agglomeration. To overcome existing measurement challenges, we track individual contributions in software engineering projects between 2015 and 2021 on GitHub, the by far largest online code repository platform. Our findings demonstrate individual productivity increases by 2.8 percent with a ten percent increase in cluster size, the share of the software engineering community in a technology field located in the same city. Instrumental variable and dynamic estimation results suggest these productivity effects are causal. Productivity gains from cluster size growth are strongest for clusters hosting between 0.67 and 13.5% of a community. We observe a disproportionate activity increase in high-quality, large, and leisure projects and for co-located teams. Overall, software engineers benefit from productivity spillovers due to physical proximity to a large number of peers in their field.
Keywords: D62; J24; O33; O36; R32; 330; high-skilled labor; geography; innovation; peer effects; collaboration